Evaluating regulatory reform of network industries: a survey of empirical models based on categorical proxies. (December 2018) - Bastianin, Andrea; Castelnovo, Paolo; Florio, Massimo
Abstract: Proxies for regulatory reforms based on categorical variables are increasingly used in empirical evaluation models. We surveyed 63 studies that rely on such indices to analyze the effects of entry liberalization, privatization, unbundling, and independent regulation of the electricity, natural gas, and telecommunications sectors. We highlight methodological issues related to the use of these proxies. Next, taking stock of the literature, we provide practical advice for the design of the empirical strategy and discuss the selection of control and instrumental variables to attenuate endogeneity problems undermining identification of the effects of regulatory reforms. Highlights: Proxies based on categorical variables are used in empirical models tracking the effects of regulatory reforms. We survey 63 studies that rely on such indices. We focus on entry liberalization, privatization, unbundling and independent regulation in network industries. We discuss issues related with the use of these proxies and provide advices for the design of the empirical strategy. We also discuss the selection of control and instrumental variables to attenuate endogeneity problems.